2016
DOI: 10.1680/jinam.15.00002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring impacts of climate change on UK’s ICT infrastructure

Abstract: Information and communication technology (ICT) infrastructure plays a critical role in many aspects of the society. While ICTs contribute to climate-related responses and adaptive practices, much less is known about the impacts that climate change may have on ICT itself. Drawing on knowledge in the literature and findings elicited from industrial workshop conversations and case studies, this paper attempts to provide a review of available evidence of climate impacts on the UK's ICT infrastructure. This researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As Government reviews following extreme weather events detail, choosing to travel involves risking exposure to disruptions such as road closures, rail cancellations, reduced speeds and delays, as well as risks to personal safety due to the physical damage to infrastructure and property, and increased levels of road traffic accidents (Chatterton et al, 2016;Quarmby et al, 2010). Meanwhile, ICT infrastructure is more resilient than transport infrastructure during these events because components are often designed for climates more extreme than the UK; technology updates result in more frequent maintenance and replacement; and the national network has high levels of redundancy, with a density of interconnected links that can maintain service for a high proportion of end users most of the time (Dawson, 2016;Fu et al, 2016;Horrocks et al, 2010). For example, the period of well-documented storms between December 2013 and February 2014 had significant transport impacts (Chatterton et al, 2016), but minimal impacts on broadband infrastructure, as analysis conducted by Ofcom indicated that only 1% of the incidents reported to them were attributed to severe weather (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As Government reviews following extreme weather events detail, choosing to travel involves risking exposure to disruptions such as road closures, rail cancellations, reduced speeds and delays, as well as risks to personal safety due to the physical damage to infrastructure and property, and increased levels of road traffic accidents (Chatterton et al, 2016;Quarmby et al, 2010). Meanwhile, ICT infrastructure is more resilient than transport infrastructure during these events because components are often designed for climates more extreme than the UK; technology updates result in more frequent maintenance and replacement; and the national network has high levels of redundancy, with a density of interconnected links that can maintain service for a high proportion of end users most of the time (Dawson, 2016;Fu et al, 2016;Horrocks et al, 2010). For example, the period of well-documented storms between December 2013 and February 2014 had significant transport impacts (Chatterton et al, 2016), but minimal impacts on broadband infrastructure, as analysis conducted by Ofcom indicated that only 1% of the incidents reported to them were attributed to severe weather (2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet the extent to which external factors such as weather influence the pattern of home-working and intrapersonal daily variability in work access is largely unknown, as is the extent to which digital technologies and, more specifically, internet access and applications can offer a resilient alternative to travel during periods of transport disruption. This is despite the expectation that such disruptions will cause a spike in demand for robust, quality internet services (Fu et al, 2016). Therefore, this research aimed to quantify whether the pattern of internet activity on working days is influenced by the expectation of severe weather or potential travel disruption, and what this tells us about the choice of which days people choose to telecommute.…”
Section: Introductionmentioning
confidence: 99%